Pengaruh Gaya Kepemimipinan, Kerja Sama Tim, dan Loyalitas Kerja Karyawan terhadap Kinerja Karyawan PT Nasmoco Kaligawe - saifuddin Muh.Saifuddin; Rauly Sijabat (Jurnal Ilmiah Manajemen Bisnis dan Ekonomi Kreatif, 2022)
The problem in this study is that the productivity of technicians decreases due to the result of the service production lead time at PT Nasmoco Kaligawe being longer than the specified target. And the purpose of this study is to analyze how the influence of leadership style, teamwork, and employee loyalty on employee performance at PT Nasmoco Kaligawe. The population of this study were all employees of PT Nasmco Kaligawe, amounting to 110 people. The sampling technique used is a saturated or census sampling technique, which makes the entire population a sample. Data collection techniques using questionnaires. Data analysis techniques include validity, reliability, and multiple regression. The results of this study indicate that leadership style has a positive and significant effect on employee performance based on calculations using the SPSS application, the t-test results are 33,893 > t table. teamwork has a significant effect on employee performance. based on calculations using the SPSS application, the results of the t test show t count 1.637 < t table 1.660 which means that the work loyalty variable has no significant effect on the employee performance variable